Magnesium oxide coating for increasing silicon steel grain size

CN116200579BActive Publication Date: 2026-10-23FUJIAN AOKELAN ELECTRIC TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310217969.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-08
Publication Date
2026-10-23
Estimated Expiration
2043-03-08

AI Technical Summary

Technical Problem

[0003]现有的硅钢晶粒在热处理中为了优化晶粒,涂布涂料进行热处理,通过涂布的涂料在热处理中对晶粒微观,现有的涂料组合物简单,优化晶粒效果差,基于此,本发明提供一种提高硅钢晶粒大小的氧化镁涂料

Benefits of technology

[0032]本发明氧化镁涂料在高温热处理中,氧化镁、二氧化钛作为协调剂,配合B元素,形成的涂层通过元素之间的配比作用硅钢产品,抑制晶粒生长,细化晶粒,同时加入的改性膨润土经过改性后,由于片层状的膨润土经过改性处理液改性优化,活性度提高,同时热反应后片层间距扩张,而纳米二氧化硅复合剂能够协配膨润土,增强膨润土在原料中的调节效果,提高氧化镁、B元素等作用硅钢,通过调节液处理的原料,能够将原料之间的界面性增强,从而促进氧化镁涂料细化晶粒的效果,改进产品的性能效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004115613150000121
    Figure BDA0004115613150000121
  • Figure BDA0004115613150000131
    Figure BDA0004115613150000131
Patent Text Reader

Abstract

The application discloses a magnesium oxide coating for improving silicon steel grain size, which comprises the following raw materials in parts by weight: 80-120 parts of magnesium oxide, 700-800 parts of water, 5-7.5 parts of titanium dioxide and 2.5-3.0 parts of boron additive. In high-temperature heat treatment, the magnesium oxide coating uses magnesium oxide and titanium dioxide as coordinating agents, cooperates with B element, forms a coating, and through the matching effect of elements on the silicon steel product, the growth of grains is inhibited and the grains are refined.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of silicon steel grain coating technology, specifically to a magnesium oxide coating that improves the grain size of silicon steel. Background Technology

[0002] Silicon steel is a silicon alloy steel containing 1.0%–4.5% silicon and less than 0.08% carbon. It possesses characteristics such as high magnetic permeability, low coercivity, and high resistivity, resulting in low hysteresis and eddy current losses. It is mainly used as a magnetic material in motors, transformers, electrical appliances, and electrical instruments. To meet the requirements of punching and shearing processes during electrical manufacturing, a certain degree of plasticity is also required. To improve magnetic performance and reduce hysteresis losses, the content of harmful impurities should be as low as possible, and the sheet should be flat with good surface quality.

[0003] In order to optimize the grain size of silicon steel during heat treatment, existing coatings are applied and then heat-treated. The coatings affect the microstructure of the grains during heat treatment. However, existing coating compositions are simple and have poor grain optimization effects. Therefore, this invention provides a magnesium oxide coating that improves the grain size of silicon steel. Summary of the Invention

[0004] In view of the deficiencies of the prior art, the purpose of this invention is to provide a magnesium oxide coating that improves the grain size of silicon steel, so as to solve the problems mentioned in the background art.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] This invention provides a magnesium oxide coating for improving the grain size of silicon steel, comprising the following raw materials in parts by weight:

[0007] 80-120 parts magnesium oxide, 700-800 parts water, 5-7.5 parts titanium dioxide, and 2.5-3.0 parts boron additive.

[0008] Preferably, the magnesium oxide coating comprises the following raw materials in parts by weight:

[0009] 100 parts magnesium oxide, 800 parts water, 6 parts titanium dioxide, and 2.8 parts boron additive.

[0010] Preferably, the magnesium oxide coating also contains modified bentonite, with an addition amount of 5-10 parts.

[0011] Preferably, the modification method of the modified bentonite is as follows:

[0012] S01: Add 5-10 parts of sodium alginate to 20-30 parts of deionized water, then add hydrochloric acid to adjust the pH to 4.5, followed by 1-3 parts of lanthanum sulfate and 0.2-0.5 parts of sodium alkyl sulfonate. Stir thoroughly to obtain the modified treatment solution.

[0013] S02: Bentonite is heated at 320-340℃ for 10-20 minutes, and then cooled to room temperature at a rate of 1-3℃ / min;

[0014] SO3: The SO2 product is added to 3-5 times its volume of modification solution and stirred for modification treatment. After stirring is completed, pre-modified bentonite is obtained.

[0015] S04: Add the pre-modified bentonite to the nano-silica composite agent at a weight ratio of 1:5 and stir thoroughly. Finally, wash with water and dry to obtain modified bentonite.

[0016] Preferably, the stirring speed of the stirring modification treatment is 400-500 r / min, the stirring temperature is 50-60℃, and the stirring time is 10-20 min.

[0017] The inventors of this invention discovered that without the addition of modified bentonite, the performance of the product tends to deteriorate significantly, while the addition of modified bentonite has a significant effect on the performance of the product.

[0018] Even when modified bentonite is used as a substitute for regular bentonite, the performance of the product still deteriorates significantly. Therefore, modified bentonite cannot be replaced by regular bentonite.

[0019] Different modification methods for modified bentonite, such as those without modification treatment liquid or SO2 treatment, all show a trend of deterioration in product performance. In addition, conditioning liquid treatment has a significant effect on product improvement, and different preparation methods of conditioning liquid result in different product effects. The method of this invention has the best effect.

[0020] Preferably, the nano-silica composite agent comprises the following raw materials in parts by weight:

[0021] 10-20 parts nano-silica, 2-5 parts chitosan, 20-30 parts deionized water, 1-4 parts sodium dodecyl sulfate, and 0.2-0.6 parts gluconolactone.

[0022] The inventors of this invention also discovered that chitosan, gluconolactone, and sodium dodecyl sulfate in the nano silica composite agent have an improving effect on the grain size and crack incidence of the product. The raw materials are combined with each other to synergistically improve the performance of the product. Based on this, the nano silica composite agent has an improving effect on the performance of the product.

[0023] Preferably, the magnesium oxide coating also contains a conditioning liquid, and the amount of conditioning liquid added is 60-100 parts.

[0024] Preferably, the method for preparing the conditioning liquid is as follows:

[0025] S11: Add 2-5 parts of tetraethoxysilane to 15-25 parts of ethanol, then add 1-3 parts of yttrium nitrate, stir well to obtain the base solution;

[0026] S12: A hydrogen peroxide-hydrochloric acid mixed solution is prepared by mixing 5% hydrogen peroxide solution and 2% hydrochloric acid solution in a weight ratio of 1:3.

[0027] S13: Add 0.1-0.5 parts of hydrogen peroxide-hydrochloric acid mixed solution to the base conditioning solution and stir at 200-230 r / min for 1-2 h. After stirring, the conditioning solution is obtained.

[0028] Preferably, the boron additive is boron.

[0029] Preferably, the preparation method of the magnesium oxide coating is as follows:

[0030] Magnesium oxide, titanium dioxide, and boron additives were added to the conditioning solution in sequence, followed by the addition of modified bentonite, and then stirred until homogeneous. The mixture was then washed with water, dried, and finally placed in water and stirred thoroughly to obtain a magnesium oxide coating.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] In this invention, the magnesium oxide coating, during high-temperature heat treatment, uses magnesium oxide and titanium dioxide as coordinators, along with element boron. The resulting coating, through the synergistic effect of the elements, inhibits grain growth and refines the grains in the silicon steel product. Simultaneously, the added modified bentonite, after modification and optimization by the modification treatment solution, exhibits increased activity due to its lamellar structure. Furthermore, the interlamellar spacing expands after the thermal reaction. The nano-silica composite agent further enhances the regulating effect of bentonite in the raw materials, improving the interaction between magnesium oxide, boron, and other elements in the silicon steel. By regulating the raw materials through the treatment solution, the interfacial properties between the raw materials are strengthened, thereby promoting the grain refinement effect of the magnesium oxide coating and improving the product's performance. Detailed Implementation

[0033] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0034] This embodiment of a magnesium oxide coating for improving the grain size of silicon steel comprises the following raw materials in parts by weight:

[0035] 80-120 parts magnesium oxide, 700-800 parts water, 5-7.5 parts titanium dioxide, and 2.5-3.0 parts boron additive.

[0036] The magnesium oxide coating of this embodiment comprises the following raw materials in parts by weight:

[0037] 100 parts magnesium oxide, 800 parts water, 6 parts titanium dioxide, and 2.8 parts boron additive.

[0038] The magnesium oxide coating in this embodiment also contains modified bentonite, with an addition amount of 5-10 parts.

[0039] The modification method of the modified bentonite in this embodiment is as follows:

[0040] S01: Add 5-10 parts of sodium alginate to 20-30 parts of deionized water, then add hydrochloric acid to adjust the pH to 4.5, followed by 1-3 parts of lanthanum sulfate and 0.2-0.5 parts of sodium alkyl sulfonate. Stir thoroughly to obtain the modified treatment solution.

[0041] S02: Bentonite is heated at 320-340℃ for 10-20 minutes, and then cooled to room temperature at a rate of 1-3℃ / min;

[0042] SO3: The SO2 product is added to 3-5 times its volume of modification solution and stirred for modification treatment. After stirring is completed, pre-modified bentonite is obtained.

[0043] S04: Add the pre-modified bentonite to the nano-silica composite agent at a weight ratio of 1:5 and stir thoroughly. Finally, wash with water and dry to obtain modified bentonite.

[0044] In this embodiment, the stirring speed for the stirring modification treatment is 400-500 r / min, the stirring temperature is 50-60℃, and the stirring time is 10-20 min.

[0045] The nano-silica composite agent of this embodiment comprises the following raw materials in parts by weight:

[0046] 10-20 parts nano-silica, 2-5 parts chitosan, 20-30 parts deionized water, 1-4 parts sodium dodecyl sulfate, and 0.2-0.6 parts gluconolactone.

[0047] In this embodiment, the magnesium oxide coating also contains a conditioning liquid, and the amount of conditioning liquid added is 60-100 parts.

[0048] The preparation method of the conditioning liquid in this embodiment is as follows:

[0049] S11: Add 2-5 parts of tetraethoxysilane to 15-25 parts of ethanol, then add 1-3 parts of yttrium nitrate, stir well to obtain the base solution;

[0050] S12: A hydrogen peroxide-hydrochloric acid mixed solution is prepared by mixing 5% hydrogen peroxide solution and 2% hydrochloric acid solution in a weight ratio of 1:3.

[0051] S13: Add 0.1-0.5 parts of hydrogen peroxide-hydrochloric acid mixed solution to the base conditioning solution and stir at 200-230 r / min for 1-2 h. After stirring, the conditioning solution is obtained.

[0052] The boron additive in this embodiment is boron.

[0053] The preparation method of the magnesium oxide coating in this embodiment is as follows:

[0054] Magnesium oxide, titanium dioxide, and boron additives were added to the conditioning solution in sequence, followed by the addition of modified bentonite, and then stirred until homogeneous. The mixture was then washed with water, dried, and finally placed in water and stirred thoroughly to obtain a magnesium oxide coating.

[0055] Example 1.

[0056] This embodiment of a magnesium oxide coating for improving the grain size of silicon steel comprises the following raw materials in parts by weight:

[0057] 80 parts magnesium oxide, 700 parts water, 5 parts titanium dioxide, and 2.5 parts boron additive.

[0058] The magnesium oxide coating in this embodiment also contains modified bentonite, with an addition amount of 5-10 parts.

[0059] The modification method of the modified bentonite in this embodiment is as follows:

[0060] S01: Add 5 parts sodium alginate to 20 parts deionized water, then add hydrochloric acid to adjust the pH to 4.5, then add 1 part lanthanum sulfate and 0.2 parts sodium alkyl sulfonate, stir thoroughly to obtain the modified treatment solution;

[0061] S02: Bentonite is heated at 320℃ for 10 min, and then cooled to room temperature at a rate of 1℃ / min;

[0062] S03: The SO2 product is added to 3 times its volume of the modification solution and stirred for modification treatment. After stirring is completed, pre-modified bentonite is obtained.

[0063] S04: Add the pre-modified bentonite to the nano-silica composite agent at a weight ratio of 1:5 and stir thoroughly. Finally, wash with water and dry to obtain modified bentonite.

[0064] In this embodiment, the stirring speed for the stirring modification treatment is 400 r / min, the stirring temperature is 50-60℃, and the stirring time is 10 min.

[0065] The nano-silica composite agent of this embodiment comprises the following raw materials in parts by weight:

[0066] The ingredients are: 10 parts nano-silica, 2 parts chitosan, 20 parts deionized water, 1 part sodium dodecyl sulfate, and 0.2 parts gluconolactone.

[0067] In this embodiment, the magnesium oxide coating also contains a conditioning liquid, and the amount of conditioning liquid added is 60 parts.

[0068] The preparation method of the conditioning liquid in this embodiment is as follows:

[0069] S11: Add 2 parts tetraethoxysilane to 15 parts ethanol, then add 1 part yttrium nitrate, stir well to obtain the base solution;

[0070] S12: A hydrogen peroxide-hydrochloric acid mixed solution is prepared by mixing 5% hydrogen peroxide solution and 2% hydrochloric acid solution in a weight ratio of 1:3.

[0071] S13: Add 0.1 part of hydrogen peroxide-hydrochloric acid mixed solution to the base conditioning solution and stir at 200 r / min for 1 h. After stirring, the conditioning solution is obtained.

[0072] The boron additive in this embodiment is boron.

[0073] The preparation method of the magnesium oxide coating in this embodiment is as follows:

[0074] Magnesium oxide, titanium dioxide, and boron additives were added to the conditioning solution in sequence, followed by the addition of modified bentonite, and then stirred until homogeneous. The mixture was then washed with water, dried, and finally placed in water and stirred thoroughly to obtain a magnesium oxide coating.

[0075] Example 2

[0076] This embodiment of a magnesium oxide coating for improving the grain size of silicon steel comprises the following raw materials in parts by weight:

[0077] 120 parts magnesium oxide, 800 parts water, 7.5 parts titanium dioxide, and 3.0 parts boron additive.

[0078] The magnesium oxide coating in this embodiment also contains modified bentonite, with an addition amount of 5-10 parts.

[0079] The modification method of the modified bentonite in this embodiment is as follows:

[0080] S01: Add 10 parts sodium alginate to 30 parts deionized water, then add hydrochloric acid to adjust the pH to 4.5, then add 3 parts lanthanum sulfate and 0.5 parts sodium alkyl sulfonate, stir thoroughly to obtain the modified treatment solution;

[0081] S02: Bentonite is heated at 340℃ for 20 minutes, and then cooled to room temperature at a rate of 3℃ / min;

[0082] SO3: The SO2 product is added to 3-5 times its volume of modification solution and stirred for modification treatment. After stirring is completed, pre-modified bentonite is obtained.

[0083] S04: Add the pre-modified bentonite to the nano-silica composite agent at a weight ratio of 1:5 and stir thoroughly. Finally, wash with water and dry to obtain modified bentonite.

[0084] In this embodiment, the stirring speed for the stirring modification treatment is 500 r / min, the stirring temperature is 60℃, and the stirring time is 20 min.

[0085] The nano-silica composite agent of this embodiment comprises the following raw materials in parts by weight:

[0086] 20 parts nano-silica, 5 parts chitosan, 30 parts deionized water, 4 parts sodium dodecyl sulfate and 0.6 parts gluconolactone.

[0087] In this embodiment, the magnesium oxide coating also contains a conditioning liquid, and the amount of conditioning liquid added is 100 parts.

[0088] The preparation method of the conditioning liquid in this embodiment is as follows:

[0089] S11: Add 5 parts tetraethoxysilane to 25 parts ethanol, then add 3 parts yttrium nitrate, stir well to obtain the base solution;

[0090] S12: A hydrogen peroxide-hydrochloric acid mixed solution is prepared by mixing 5% hydrogen peroxide solution and 2% hydrochloric acid solution in a weight ratio of 1:3.

[0091] S13: Add 0.5 parts of hydrogen peroxide-hydrochloric acid mixed solution to the base conditioning solution and stir at 230 r / min for 2 h. After stirring, the conditioning solution is obtained.

[0092] The boron additive in this embodiment is boron.

[0093] The preparation method of the magnesium oxide coating in this embodiment is as follows:

[0094] Magnesium oxide, titanium dioxide, and boron additives were added to the conditioning solution in sequence, followed by the addition of modified bentonite, and then stirred until homogeneous. The mixture was then washed with water, dried, and finally placed in water and stirred thoroughly to obtain a magnesium oxide coating.

[0095] Example 3

[0096] This embodiment of a magnesium oxide coating for improving the grain size of silicon steel comprises the following raw materials in parts by weight:

[0097] 100 parts magnesium oxide, 800 parts water, 6 parts titanium dioxide, and 2.8 parts boron additive.

[0098] The magnesium oxide coating in this embodiment also contains modified bentonite, with an addition amount of 7.5 parts.

[0099] The modification method of the modified bentonite in this embodiment is as follows:

[0100] S01: Add 7.5 parts sodium alginate to 25 parts deionized water, then add hydrochloric acid to adjust the pH to 4.5, then add 2 parts lanthanum sulfate and 0.35 parts sodium alkyl sulfonate, stir thoroughly to obtain the modified treatment solution;

[0101] S02: Bentonite is heated at 330℃ for 15 minutes, and then cooled to room temperature at a rate of 2℃ / min.

[0102] S03: The product of SO2 is fed into a 4-fold volume of modification solution and stirred for modification treatment. After stirring is completed, pre-modified bentonite is obtained.

[0103] S04: Add the pre-modified bentonite to the nano-silica composite agent at a weight ratio of 1:5 and stir thoroughly. Finally, wash with water and dry to obtain modified bentonite.

[0104] In this embodiment, the stirring speed for the stirring modification treatment is 450 r / min, the stirring temperature is 55℃, and the stirring time is 15 min.

[0105] The nano-silica composite agent of this embodiment comprises the following raw materials in parts by weight:

[0106] The ingredients are: 15 parts nano-silica, 3.5 parts chitosan, 25 parts deionized water, 2.5 parts sodium dodecyl sulfate, and 0.4 parts gluconolactone.

[0107] In this embodiment, the magnesium oxide coating also contains a conditioning liquid, and the amount of conditioning liquid added is 80 parts.

[0108] The preparation method of the conditioning liquid in this embodiment is as follows:

[0109] S11: Add 3.5 parts of tetraethoxysilane to 20 parts of ethanol, then add 2 parts of yttrium nitrate, stir well to obtain the base solution;

[0110] S12: A hydrogen peroxide-hydrochloric acid mixed solution is prepared by mixing 5% hydrogen peroxide solution and 2% hydrochloric acid solution in a weight ratio of 1:3.

[0111] S13: Add 0.3 parts of hydrogen peroxide-hydrochloric acid mixed solution to the base conditioning solution and stir at 210 r / min for 1.5 h. After stirring, the conditioning solution is obtained.

[0112] The boron additive in this embodiment is boron.

[0113] The preparation method of the magnesium oxide coating in this embodiment is as follows:

[0114] Magnesium oxide, titanium dioxide, and boron additives were added to the conditioning solution in sequence, followed by the addition of modified bentonite, and then stirred until homogeneous. The mixture was then washed with water, dried, and finally placed in water and stirred thoroughly to obtain a magnesium oxide coating.

[0115] Example 4.

[0116] This embodiment of a magnesium oxide coating for improving the grain size of silicon steel comprises the following raw materials in parts by weight:

[0117] 85 parts magnesium oxide, 720 parts water, 6 parts titanium dioxide, and 2.6 parts boron additive.

[0118] The magnesium oxide coating in this embodiment also contains modified bentonite, with an addition amount of 6 parts.

[0119] The modification method of the modified bentonite in this embodiment is as follows:

[0120] S01: Add 6 parts sodium alginate to 22 parts deionized water, then add hydrochloric acid to adjust the pH to 4.5, then add 1.2 parts lanthanum sulfate and 0.3 parts sodium alkyl sulfonate, stir thoroughly to obtain the modified treatment solution;

[0121] S02: Bentonite is heated at 330℃ for 12 minutes, and then cooled to room temperature at a rate of 2℃ / min;

[0122] S03: The product of SO2 is fed into a 4-fold volume of modification solution and stirred for modification treatment. After stirring is completed, pre-modified bentonite is obtained.

[0123] S04: Add the pre-modified bentonite to the nano-silica composite agent at a weight ratio of 1:5 and stir thoroughly. Finally, wash with water and dry to obtain modified bentonite.

[0124] In this embodiment, the stirring speed for the stirring modification treatment was 410 r / min, the stirring temperature was 52℃, and the stirring time was 12 min.

[0125] The nano-silica composite agent of this embodiment comprises the following raw materials in parts by weight:

[0126] The ingredients are: 12 parts nano-silica, 3 parts chitosan, 22 parts deionized water, 2 parts sodium dodecyl sulfate, and 0.3 parts gluconolactone.

[0127] In this embodiment, the magnesium oxide coating also contains a conditioning liquid, and the amount of conditioning liquid added is 65 parts.

[0128] The preparation method of the conditioning liquid in this embodiment is as follows:

[0129] S11: Add 3 parts tetraethoxysilane to 17 parts ethanol, then add 2 parts yttrium nitrate, stir well to obtain the base solution;

[0130] S12: A hydrogen peroxide-hydrochloric acid mixed solution is prepared by mixing 5% hydrogen peroxide solution and 2% hydrochloric acid solution in a weight ratio of 1:3.

[0131] S13: Add 0.2 parts of hydrogen peroxide-hydrochloric acid mixed solution to the base conditioning solution and stir at 210 r / min for 1.2 h. After stirring, the conditioning solution is obtained.

[0132] The boron additive in this embodiment is boron.

[0133] The preparation method of the magnesium oxide coating in this embodiment is as follows:

[0134] Magnesium oxide, titanium dioxide, and boron additives were added to the conditioning solution in sequence, followed by the addition of modified bentonite, and then stirred until homogeneous. The mixture was then washed with water, dried, and finally placed in water and stirred thoroughly to obtain a magnesium oxide coating.

[0135] Example 5.

[0136] This embodiment of a magnesium oxide coating for improving the grain size of silicon steel comprises the following raw materials in parts by weight:

[0137] 110 parts magnesium oxide, 780 parts water, 7.0 parts titanium dioxide, and 2.8 parts boron additive.

[0138] The magnesium oxide coating in this embodiment also contains modified bentonite, with an addition amount of 5-10 parts.

[0139] The modification method of the modified bentonite in this embodiment is as follows:

[0140] S01: Add 8 parts of sodium alginate to 28 parts of deionized water, then add hydrochloric acid to adjust the pH to 4.5, then add 2.8 parts of lanthanum sulfate and 0.4 parts of sodium alkyl sulfonate, stir thoroughly to obtain the modified treatment solution;

[0141] S02: Bentonite is heated at 330℃ for 18 minutes, and then cooled to room temperature at a rate of 2℃ / min;

[0142] S03: The product of SO2 is fed into a 4-fold volume of modification solution and stirred for modification treatment. After stirring is completed, pre-modified bentonite is obtained.

[0143] S04: Add the pre-modified bentonite to the nano-silica composite agent at a weight ratio of 1:5 and stir thoroughly. Finally, wash with water and dry to obtain modified bentonite.

[0144] In this embodiment, the stirring speed for the stirring modification treatment was 480 r / min, the stirring temperature was 56℃, and the stirring time was 18 min.

[0145] The nano-silica composite agent of this embodiment comprises the following raw materials in parts by weight:

[0146] The mixture consists of 18 parts nano-silica, 4 parts chitosan, 28 parts deionized water, 3 parts sodium dodecyl sulfate, and 0.4 parts gluconolactone.

[0147] In this embodiment, the magnesium oxide coating also contains a conditioning liquid, and the amount of conditioning liquid added is 95 parts.

[0148] The preparation method of the conditioning liquid in this embodiment is as follows:

[0149] S11: Add 4 parts tetraethoxysilane to 22 parts ethanol, then add 2 parts yttrium nitrate, stir well to obtain the base solution;

[0150] S12: A hydrogen peroxide-hydrochloric acid mixed solution is prepared by mixing 5% hydrogen peroxide solution and 2% hydrochloric acid solution in a weight ratio of 1:3.

[0151] S13: Add 0.4 parts of hydrogen peroxide-hydrochloric acid mixed solution to the base conditioning solution and stir at 220 r / min for 1.8 h. After stirring, the conditioning solution is obtained.

[0152] The boron additive in this embodiment is boron.

[0153] The preparation method of the magnesium oxide coating in this embodiment is as follows:

[0154] Magnesium oxide, titanium dioxide, and boron additives were added to the conditioning solution in sequence, followed by the addition of modified bentonite, and then stirred until homogeneous. The mixture was then washed with water, dried, and finally placed in water and stirred thoroughly to obtain a magnesium oxide coating.

[0155] Comparative Example 1.

[0156] Unlike Example 3, no modified bentonite was added.

[0157] Comparative Example 2.

[0158] Unlike Example 3, the modified bentonite is replaced with bentonite.

[0159] Comparative Example 3.

[0160] The modification method of the modified bentonite is different from that of Example 3; no nano-silica composite agent was added.

[0161] Comparative Example 4.

[0162] Unlike Example 3, the bentonite was not treated with a modified treatment solution.

[0163] Comparative Example 5.

[0164] Unlike Example 3, in the modification method of the modified bentonite, SO2 was not used: the bentonite was heated at 330°C for 18 minutes and then cooled to room temperature at a rate of 2°C / min.

[0165] Comparative Example 6.

[0166] Unlike Example 3, no conditioning solution was used.

[0167] Comparative Example 7

[0168] The difference from Example 3 is the preparation method of the conditioning solution;

[0169] Add 4 parts tetraethoxysilane to 22 parts ethanol and stir until homogeneous to obtain the base solution.

[0170] The grain size of uncoated silicon steel after heat treatment was measured to be 15 mm as a control group. The products of Examples 1-5 and Comparative Examples 1-7 were tested after coating. At the same time, the crack incidence rate (%) of the products was tested, which refers to the proportion of cracks in the tested products.

[0171]

[0172]

[0173] As can be seen from Examples 1-3 and Comparative Examples 1-7;

[0174] The crack incidence and grain size of the product in Example 3 of this invention are significantly improved. Without the addition of modified bentonite, the performance of the product deteriorates significantly. The addition of modified bentonite has a significant effect on the performance of the product.

[0175] Even when modified bentonite is used as a substitute for regular bentonite, the performance of the product still deteriorates significantly. Therefore, modified bentonite cannot be replaced by regular bentonite.

[0176] Different modification methods for modified bentonite, such as those without modification treatment liquid or SO2 treatment, all show a trend of deterioration in product performance. In addition, conditioning liquid treatment has a significant effect on product improvement, and different preparation methods of conditioning liquid result in different product effects. The method of this invention has the best effect.

[0177] This invention also explores the effects of nano-silica composite agents in products:

[0178] The nano-silica composite agent comprises the following raw materials in parts by weight:

[0179] The mixture consists of 18 parts nano-silica, 4 parts chitosan, 28 parts deionized water, 3 parts sodium dodecyl sulfate, and 0.4 parts gluconolactone.

[0180] Experimental Example 1.

[0181] Same as Example 3, except that chitosan was not added to the nano-silica composite agent.

[0182] Experimental Example 2.

[0183] Same as Example 3, except that gluconolactone was not added.

[0184] Experimental Example 3

[0185] Same as Example 3, except that sodium dodecyl sulfate was not added.

[0186] Experimental Example 1 11.2 15.9 Experimental Example 2 11.5 16.2 Experimental Example 3 10.8 14.5

[0187] As can be seen from Experiments 1-3, chitosan, gluconolactone, and sodium dodecyl sulfate in the nano silica composite agent all have an improving effect on the grain size and crack incidence of the product. The raw materials are combined with each other to improve the performance of the product in a coordinated manner. Based on this, the nano silica composite agent has an improving effect on the product performance.

[0188] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0189] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A magnesium oxide coating for improving the grain size of silicon steel, characterized in that, Including the following parts by weight of raw materials: Magnesium oxide 80-120 parts, water 700-800 parts, titanium dioxide 5-7.5 parts, boron additive 2.5-3.0 parts; The magnesium oxide coating also contains modified bentonite, with an addition amount of 5-10 parts; The modification method of the modified bentonite is as follows: S01: Add 5-10 parts of sodium alginate to 20-30 parts of deionized water, then add hydrochloric acid to adjust the pH to 4.5, followed by 1-3 parts of lanthanum sulfate and 0.2-0.5 parts of sodium alkyl sulfonate. Stir thoroughly to obtain the modified treatment solution. S02: Bentonite is heated at 320-340℃ for 10-20 minutes, and then cooled to room temperature at a rate of 1-3℃ / min; SO3: The SO2 product is added to 3-5 times its volume of modification solution and stirred for modification treatment. After stirring is completed, pre-modified bentonite is obtained. S04: Add the pre-modified bentonite to the nano silica composite agent at a weight ratio of 1:5 and stir thoroughly. Finally, wash with water and dry to obtain modified bentonite. The nano-silica composite agent comprises the following raw materials in parts by weight: 10-20 parts nano-silica, 2-5 parts chitosan, 20-30 parts deionized water, 1-4 parts sodium dodecyl sulfate, and 0.2-0.6 parts gluconolactone; The magnesium oxide coating also contains a conditioning liquid, the amount of which is 60-100 parts; The preparation method of the conditioning liquid is as follows: S11: Add 2-5 parts of tetraethoxysilane to 15-25 parts of ethanol, then add 1-3 parts of yttrium nitrate, stir well to obtain the base solution; S12: A hydrogen peroxide-hydrochloric acid mixed solution is prepared by mixing 5% hydrogen peroxide solution and 2% hydrochloric acid solution in a weight ratio of 1:

3. S13: Add 0.1-0.5 parts of hydrogen peroxide-hydrochloric acid mixed solution to the base conditioning solution and stir at 200-230 r / min for 1-2 h. After stirring, the conditioning solution is obtained. The boron additive is boron; The preparation method of the magnesium oxide coating is as follows: Magnesium oxide, titanium dioxide, and boron additives were added to the conditioning solution in sequence, followed by the addition of modified bentonite, and then stirred until homogeneous. The mixture was then washed with water, dried, and finally placed in water and stirred thoroughly to obtain a magnesium oxide coating.

2. The magnesium oxide coating for improving the grain size of silicon steel according to claim 1, characterized in that, The magnesium oxide coating comprises the following raw materials in parts by weight: 100 parts magnesium oxide, 800 parts water, 6 parts titanium dioxide, and 2.8 parts boron additive.

3. The magnesium oxide coating for improving the grain size of silicon steel according to claim 1, characterized in that, The stirring speed for the stirring modification treatment is 400-500 r / min, the stirring temperature is 50-60℃, and the stirring time is 10-20 min.

Citation Information

Patent Citations

  • Annealing agent for high-magnetic-strength oriented silicon steel, preparing method of annealing agent and application of annealing agent to reducing hydration rate

    CN107746929A